2012
DOI: 10.1016/j.ijid.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neutralizing antibody and cell-mediated immune responses to pandemic H1N1 2009 influenza virus before and after H1N1 2009 influenza vaccination of elderly subjects and healthcare workers

Abstract: Influenza vaccination elicits significant neutralizing antibody and T-cell responses to pandemic H1N1 2009 influenza virus. However, in response to vaccination, increases in neutralizing antibody titers were comparatively lower but T-cell responses were higher in older participants. Therefore, our study suggests that memory T-cells may play a crucial role in protecting older individuals against pandemic H1N1 2009 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…Previous studies have indicated that influenza virus-specific CD8 T cells primed by influenza virus infection can be boosted with TIV or LAIV vaccines (43)(44)(45). In our study we investigated if CD8 T cell responses could be primed by TIV vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that influenza virus-specific CD8 T cells primed by influenza virus infection can be boosted with TIV or LAIV vaccines (43)(44)(45). In our study we investigated if CD8 T cell responses could be primed by TIV vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…A more rapid decline of specific immunity following vaccination may also account for observations on the questionable efficacy of influenza vaccine in older compared to younger individuals [26, 27], as well as shifts in age distribution towards older individuals following a pandemic, which we already observed in later epidemics of A(H1N1)pdm09 infection in Singapore [6] and elsewhere [7]. If indeed we are unable to maintain a durable humoral immune response to influenza in the elderly, then influenza vaccine development would need to focus on alternative strategies such as stimulation of T-cell responses against influenza, as these may be better preserved than humoral immunity in the elderly [2830]. In addition, our findings also suggest that symptomatic infections may generate more robust immune responses than asymptomatic infections as indicated by the higher titers observed in the former by both HI and MN.…”
Section: Discussionmentioning
confidence: 99%
“…Although assessment of antibody responses to influenza vaccines is mainly used as a measure of efficacy, studies continue to show that humoral immunity by itself does not provide sterilizing immunity against infection in older adults, and that T-cell responses are critically important when antibody-mediated protection fails (81). Furthermore, T-cell responses are cross-reactive within the strains of influenza A or influenza B, allowing for broad protection against drifted strains of influenza (82).…”
Section: The Role Of T-cells In Influenza Infection and Vaccinationmentioning
confidence: 99%